1996
DOI: 10.1007/s004030050033
|View full text |Cite
|
Sign up to set email alerts
|

α 2 -Antiplasmin and plasminogen activator inhibitors in healing human skin wounds

Abstract: Mechanical injury of tissues is followed by the formation of a provisional fibrin matrix, which is later replaced by granulation tissue. The fibrinolytic proteinase, plasmin, is thought to contribute to the displacement of the primary matrix. Plasmin is generated from the ubiquitous proenzyme plasminogen by plasminogen activators. The system of plasminogen activation is controlled at several levels: plasminogen activator inhibitors (PAI-1 and PAI-2) counteract the activity of plasminogen activators and alpha 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…15,16 Other studies have also found that the staining for PAI-2 increases with time after wounding and parallels the development of the cellular infiltrate. 17 During the stage of granulation tissue formation, fibroblasts, monocytes/macrophages, and endothelial cells appeared in the wound space. In the sections 854 from day 3 to 7 of periodontal wound healing, positive staining for u-PA, PAI-1, and PAI-2 was seen in the monocytes/macrophages and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Other studies have also found that the staining for PAI-2 increases with time after wounding and parallels the development of the cellular infiltrate. 17 During the stage of granulation tissue formation, fibroblasts, monocytes/macrophages, and endothelial cells appeared in the wound space. In the sections 854 from day 3 to 7 of periodontal wound healing, positive staining for u-PA, PAI-1, and PAI-2 was seen in the monocytes/macrophages and fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…During this stage, the expression of PAI-1 and PAI-2 in the present study was similar to that found by others who have noted PAI-1 and PAI-2 expression by monocytes/macrophages and fibroblasts in developing granulation tissue. 11,17 Recent studies have shown the involvement of several components of the plasminogen-plasmin system in endothelial cell migration and angiogenesis. 1,8,11 In wound healing experiments in vitro, endothelial cells have been shown to upregulate u-PA, u-PAR, and PAI-1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Increased alpha‐2‐antiplasmin may help to mitigate plasmin destruction of the DEJ and activation of MMPs . The increased levels of antithrombin III may be to balance the (pro)thrombin activity .…”
Section: Discussionmentioning
confidence: 99%
“…387, American Diagnostica, Greenwich CT, USA), PAI-1 (rabbit antibody, Department of Experimental and Chemical Endocrinology, University Medical Center St Radboud, Nijmegen, The Netherlands (Grebenschikov et al, 1997)), PAI-2 (goat antibody, Behring Werke AG, Marburg, Germany) and uPAR (rabbit antibody, Finsen Laboratory, Copenhagen, Denmark (Rønne et al, 1995)). To check sensitivity and specificity, stainings with other antibodies against tPA (rabbit polyclonal antibody, Department of Experimental and Chemical Endocrinology, University Medical Center St Radboud, Nijmegen, The Netherlands (Grebenschikov et al, 1997)), PAI-2 (goat polyclonal antibody, Institute for Immunology, University Hospital Heidelberg, Germany (Schaefer et al, 1996)) and uPAR (monoclonal antibody R2, Finsen Laboratory (Rønne et al, 1991)), and with two other antibodies against PAI-1 (monoclonal antibody Clone 1, Monozyme, Hoersholm, Denmark; monoclonal antibody no. 380, American Diagnostica) were compared on more than 100 lesions.…”
Section: Immunohistochemistrymentioning
confidence: 99%